2015
DOI: 10.14486/ijscs390
|View full text |Cite
|
Sign up to set email alerts
|

Halk Oyunları Branşına Katılan Sporcuların Yarışma Öncesi Kaygı Düzeylerinin Bazı Değişkenler Açısından İncelenmesi

Abstract: This study was carried out with in order to determine the pre-competition anxiety levels of sportsmen participating in the Turkish Folk Dance branch in terms of some variables. The population of the study, which was carried out using a general screening model, consisted of 253 sportsmen, participated with the local halay dance in the group competition, organized by the Turkish Folk Dance Federation in city of Malatya, and its sampling consisted of 187 sportsmen chosen from the population by a random method. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…These results show that the longer the participants are engaged in Muay Thai, the less anxiety they have, which might be due to the fact that having more experience decreases their anxiety and provides them with a more relaxed mood before competitions. This result is similar to those reported by studies on professional football players (Koç, 2004), athletes (Başaran, 2008), judokas (Çelik, 2010) and folk dancers (Hacıcaferoğlu et al, 2015;Uslu, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results show that the longer the participants are engaged in Muay Thai, the less anxiety they have, which might be due to the fact that having more experience decreases their anxiety and provides them with a more relaxed mood before competitions. This result is similar to those reported by studies on professional football players (Koç, 2004), athletes (Başaran, 2008), judokas (Çelik, 2010) and folk dancers (Hacıcaferoğlu et al, 2015;Uslu, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Our result is similar to those reported by studies on taekwondo players (Yücel, 2003), basketball players (Erbaş & Küçük, 2012), individual and team athletes (Civan et al 2010), first-time divers (Oktay & Yıldız, 2018) and folk dance teams (Uslu, 2018). Çelik (2010) and Hacıcaferoğlu et al (2015), on the other hand, reported that age is negatively correlated with state anxiety. This might be due to the fact that with age comes maturity and experience, resulting in a decrease in anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Başaran, Taşkın, Sanioğlu and Taşkın (2009) found that the state anxiety levels of male athletes were higher than female athletes in their study of investigation of state and constant anxiety levels of athletes according to various parameters. Hacıcaferoğlu, Seçer and Hacıcaferoğlu (2015) found that female athletes' pre-competition state anxiety levels were higher than male athletes in their study on the state anxiety levels of athletes in the folk dances branch. It is thought that the sports branch has an effect on the differentiation of the state anxiety levels of the athletes according to gender.…”
Section: Findings and Discussionmentioning
confidence: 85%
“…Yöndem (2012), performans öncesi algılanan yeterlik, kişilik özelliğine ilişkin olumsuz nitelendirmeler, olumsuz düşünme, beğenilmeme korkusu, yetersiz hazırlık, mükemmeliyetçilik gibi düşünce içeriklerini, kaygı ile ilişkilendirmektedir. Kurtuldu (2017) Halk oyunu sporcuları üzerinde yapılan yarışma öncesi durumluk ve sürekli kaygı çalışmalarından elde edilen sonuçlar incelendiğinde, jüri tarafından değerlendirilme, seyircinin varlığı, yarışmaya konsantre olma, fiziki performans sergileme, başarı veya başarısızlık durumundaki sorumluluk duygusu gibi durumların kaygıya sebep olduğu, performansı değerlendirecek bir jüri olması durumunda, kişilerin performansla ilgili kaygı düzeylerinin arttığı, Jüriye karşı aşırı duyarlı olma ve jürinin hareketlerinden olumsuz anlamlar çıkarma gibi performans kaygısının belirtileri olduğu sonuçları bulunmuştur (Yöndem, 2012;Hacıcaferoğlu, 2015;Yıldırım 2020;Özgür, 2017;Yalçın, 2021).…”
Section: Discussionunclassified